Memory Dynamics in Students During the Academic Process - Dustov Karim Turayevich; G’ofurova Sevinch O’rin qizi (American Journal of Bioscience and Clinical Integrity, 2026)
This study investigates the dynamics of short-term memory in first- and second-year university students throughout the academic year. Memory is a key cognitive function that determines the effectiveness of learning, encompassing the processes of receiving, storing, and retrieving information. The relevance of the topic is particularly pronounced among first-year students, as they face significant adaptation challenges upon entering higher education. The theoretical foundation of the study is based on the working memory model developed by Baddeley and Hitch, which remains a widely accepted conceptual framework in cognitive science. Research indicates that academic stress is one of the most critical external factors affecting memory performance, as it triggers cortisol release through the hypothalamic-pituitary-adrenal axis and reduces working memory capacity. The study was conducted during the 2025–2026 academic year at Karshi State University, involving 88 biology students (18 males and 70 females) from the first and second years. Memory was assessed at four stages: the beginning of the academic year (September), before examinations (January), after examinations (February), and at the end of the academic year (May). Both figurative visual memory (FVM) and numerical visual memory (NVM) were measured using the modern NS-Psychotest apparatus. The results demonstrated a wave-like pattern of memory dynamics in all groups: a significant decline before examinations, partial recovery after examinations, and a repeated decline by the end of the academic year. In first-year male students, FVM decreased from 82.5% in September to 75.8% in January, recovered to 82.2% in February, and fell again to 76.0% in May. Similar trends were observed in female students and in both groups of second-year students. All differences between September and January/May values were statistically significant (P<0.05). A notable finding was that female students showed a more pronounced recovery of figurative memory after examinations compared to males, which may reflect gender differences in post-stress cognitive resilience. Second-year female students exhibited a sharper memory decline in January compared to first-year females, suggesting cumulative cognitive fatigue over successive academic years. The study concludes that short-term memory indicators are highly sensitive to academic workload and that the observed patterns reflect the combined influence of examination stress and cumulative cognitive fatigue. The findings hold practical significance for planning the educational process, distributing cognitive load rationally, and scheduling rest periods to support memory recovery in university students.